Allelopathic effect of Baccharis ulicina on germination and initial growth of Avena sativa, Lolium perenne and Raphanus sativus - Tucat, Guillermo; Bentivegna, Diego; Fernández, Osvaldo; Busso, Carlos; Brevedan, Roberto; Mujica, María de la Merced; Torres, Yanina; Daddario, Juan; Ithurrart, Leticia; Giorgetti, Hugo; Rodríguez, Gustavo; Montenegro, Oscar; et al. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Baccharis ulicina is a weed widely distributed in pastures of the semiarid zone of Argentina. With the aim of evaluate potential allelopathic effects, aqueous extracts of B. ulicina (leaf, stem, root and whole plant) at two concentrations (50 and 150 g tissue/L water) were used on germination and initial growth of Avena sativa, Lolium perenne and Raphanus sativus. For each species, 100 seeds were watered and maintained at 25°C at darkness. Seed germination and length of coleoptile / hypocotyl (C/H) and radicle (R) was measured. Then, germination percentage, germination rate coefficient, germination vigor, inhibition of germination, inhibition of radicle length and coleoptile / hypocotyl length, radicle vigor index and the coleoptile / hypocotyl vigor index were calculated. High concentration extracts reduced germination an average of 65%, in addition, they produced a length inhibition of 58.8% (C/H) and 93.3% (R) to A. sativa; 71.5% (C/H) and 87.9% (R) to L. perenne, and 93.8% (C/H) and 94.5% (R) to R. sativus. There was an evident phytotoxic effect of B. ulicina on evaluated species, indicating that allelopathy would be an ecological strategy of the species.